Ensino de física contemporânea: a história da nanotecnologia utilizando o método Peer Instruction - Medeiros, Erickson Morais de (2023)
Nanotechnology is a branch of inter and multidisciplinary science, therefore it enables various topics to be covered in the classroom. This work aims to explore the History of Nanotechnology, through the use of the Theory of Didactic Transposition, Chevallard, and making use of active methodologies, notably Peer Instruction, and its theoretical contributions such as Vygotsky and Ausubel's Learning Theories. We elaborate a Didactic Sequence based on this methodology, created by Eric Mazur, and evaluated with the Hake Gain methodology, which is a standardized measurement that serves as a basis of comparison between two states or learning times. Due to the problems caused by the Covid-19 Pandemic, the Educational Product created for this dissertation has characteristics of hybrid classes, but was applied online in your totality. With the health problems, the student group had the participation of seven volunteer students from IFAM (Campus Manaus and Campus Itacoatiara), forming a heterogeneous group where many did not know each other. The obtained results in the application of the Educational Product were satisfactory, since the average gain was 0.5 (Hake Normalized Gain), but due to the wrong choice of a question (type of question), which led students into error, this gain would perhaps be better.